Exploring the effects of long-term anti-social behaviour victimisation - Heap, Vicky (International review of victimology, 2021)
Despite victimological interest in the impacts of different types of criminal victimisation, there is little empirical work that examines the effects of sub-criminal behaviour on victims. This article begins to redress the balance by reporting the findings from a qualitative research project in England that investigated the effects of long-term anti-social behaviour victimisation. Semi-structured interviews explored victims’ accounts of the long-term anti-social behaviour they experienced and the resultant effects it had on their lives. The research uncovered that victims experience a range of mental and physical health effects as well as behavioural changes and has provided the first in-depth insight into the impact of this type of victimisation. The findings suggest the cumulative harms associated with anti-social behaviour need to be better acknowledged, understood and addressed, with greater support made available to victims.